HEAT-TRANSFER CHARACTERISTICS OF COOL-THERMAL STORAGE-SYSTEMS - RYU, HW; HONG, SA; SHIN, BC; KIM, SD (PERGAMON-ELSEVIER SCIENCE LTD, 1991)
The heat-transfer characteristics of cool-thermal storage units during the charging period were studied with 2 wt% of sodium sulfate decahydrate in aqueous solution as the phase-change material. Vertical and horizontal tube systems were compared with respect to heat-transfer rate, coefficient of performance and supercooling of the phase-change material. It was found that crystals of the phase-change material grow into concentric circles in the horizontal tubes whereas they grow into convex circles in the vertical tubes. The crystal-growth patterns for the vertical tube systems are caused by the thermocline of the heat-transfer fluid surrounding the tubes. As a result, the vertical-tube system has better thermal performance than the horizontal-tube system. The total amounts of stored energy were correlated in terms of the Fourier, Stefan, and Reynolds numbers to provide basic data for designing tube types of cool-thermal-energy-storage systems.
Keywords: LATENT